2018
DOI: 10.5152/clinexphealthsci.2017.437
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Mechanical Vibration of Heel Stick Pain in Neonates

Abstract: Amaç: Topuk kanı alınması işlemi; yenidoğanların hastanede kaldığı sürede en sık uygulanan ağrılı girişimlerdendir. Mekanik vibrasyon yenidoğan ağrı kontrolünde tercih edilebilecek invaziv olmayan, ucuz ve kolay uygulanabilir bir yöntemdir. Çalışmamız yenidoğanlarda topuk delme işlemi sırasında oluşabilecek ağrı hissini engellenmek için mekanik vibrasyon uygulamasının etkinliğini test etmek amacıyla yapılmıştır. Yöntem: Araştırma randomize kontrollü, tek merkezli prospektif bir çalışma olarak Medeniyet Ünivers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…However, very few studies have investigated the effectiveness of vibration therapy in alleviating pain during heel lance procedures in newborns 18. The current study has provided similar results to previous clinical studies that found that the pain threshold increased as a result of the vibration 15,16,18. In a study by McGinnis et al,16 the heels of the newborns in the control group were warmed with a heel warmer 3 to 5 minutes before the heel lance procedures, and the newborns were given 0.1- to 0.2-mL oral 24% sucrose with a pacifier 2 minutes before the procedures.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…However, very few studies have investigated the effectiveness of vibration therapy in alleviating pain during heel lance procedures in newborns 18. The current study has provided similar results to previous clinical studies that found that the pain threshold increased as a result of the vibration 15,16,18. In a study by McGinnis et al,16 the heels of the newborns in the control group were warmed with a heel warmer 3 to 5 minutes before the heel lance procedures, and the newborns were given 0.1- to 0.2-mL oral 24% sucrose with a pacifier 2 minutes before the procedures.…”
Section: Discussionsupporting
confidence: 85%
“…The efficacy of mechanical vibration for relieving pain in newborns has been shown in clinical studies 15–18. However, very few studies have investigated the effectiveness of vibration therapy in alleviating pain during heel lance procedures in newborns 18.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations